Relative importance of service value by customer relationship stages: Evidence from the Indian retail banking. Issue 2 (3rd April 2017) - Ponnam, Abhilash; Paul, Rik
Abstract : Purpose: The purpose of this paper is to empirically sketch the phenomenon about the nature of service value expected in different stages of relationship over time in Indian retail banking context. Design/methodology/approach: Customer service value dimensions pertinent to Indian retail banking context were explored psychometrically. Later, mean factor scores of obtained service value dimensions across relationship stages (early, intermediate, and advanced) were calculated and fed into PERMAP software to graphically depict the relationship between value dimensions and relationship stages. To validate the PERMAP solution, one-way ANOVA was run for each value dimension with independent variable as a relationship level. Findings: The service value dimensions pertinent to Indian banking context are customer intimacy, product leadership, service equity, perceived sacrifice, service quality, and operational excellence. The authors could empirically prove that except for operational excellence and service quality, all the other value dimensions exhibited variation in importance over time. Results reveal that customers in the early stages of relationship value tangible value dimensions and the ones in advanced stages of relationship value intangible dimensions. Practical implications: Managers should formulate marketing strategies which will signal the customers, the superiority of the bank in delivering performance on tangible dimensions during the early stages of relationship, whereas understanding and addressing unique customer needs and establishing an emotional bonding with customers should be emphasized in the advanced stages of relationship. Originality/value: The current research could adequately establish the essential role of tangible value dimensions in shaping service value during the early stages of relationship and intangible value dimensions in the later stages of relationship.